Sistem Pakar Identifikasi Hama Pada Tanaman Cabai dalam Upaya Meningkatkan Kualitas Cabai - Cep Lukman Rohmat; Nana Suarna; Nining Rahaningsih; Elisa Sriyulia (INTERNAL (Information System Journal), 2020)
The lack of supply of chili in the market causes the price to rise sharply. The price of chillies is almost unreasonable to far beyond the price of meat. Gray (Spodoptera litura) and Fungus colletotrichum are two of the main causes of chili plants which cause many chili plants to die or fail to harvest. must experience failure due to a lack of understanding of the beginning of the pest attacking the plants. In addition, the attack on chili plants is a high risk that must be faced by farmers.In this study using the Forward Chaining Method. Forward Chaining is an inference process that starts the search from the premise or input data in the form of symptoms leading to conclusions, namely the conclusion of pests that attack chilli plants and provide solutions for advice on handling and prevention based on observed symptoms. Data used from pest data caused by small animals such as caterpillars and flies.The results are expected to be able to identify quickly, precisely and accurately the chili plants. In addition, it is expected to be able to help farmers in anticipating the symptoms of the occurrence of pests in chili plants from an early age so that preventive measures will be taken immediately. Accuracy and accuracy are needed in identifying the symptoms of pest in accordance with the expected results.